A multi-screen collaboration-based low-cost portable dry-lab simulator for basic laparoscopic skills training: A technical note - Yifan Chang; Chenqi Tang; Xianqi Shui; Yamei Zhou; Xiaoyu Jiang; Jia Liu; Yu Sun (Laparoscopic, Endoscopic and Robotic Surgery, 2022)
Laparoscopic skills training has always been crucial for novice surgeons. Readily accessible equipment, as well as structured training curriculum should be provided to guarantee adequate practice hours and skill proficiency. Dry-lab training is typically adopted before animal model surgery, usually comprising of purpose-built bulky simulators that is neither accessible nor portable. In this technical note, we designed a home-made simulator, using two 4 L water jugs as operating space that are communicated inside, plus an observation hole taped in between to mimic the triangular working space of laparoscopic surgery. Imaging was achieved via smartphone camera, which was wirelessly connected to a laptop and a projector for real-time display on multiple screens, using built-in multi-screen collaboration software. A self-regulated and proficiency-based training curriculum was adopted. This dry-lab simulator is low-cost, highly portable and easily replicable for basic laparoscopic skills training for the beginners to intermediate surgeons, which may serve as a good way for the standardized residency and specialist training program.